PERSPEKTIF PENERAPAN PENGENDALIAN HAMA TERPADU DALAM USAHATANI LADA - RACHMAT HENDAYANA; SAKTYANU K. DERMOREDJO; TJETJEP NURASA; ROOSGANDHA ELIZABETH (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
The research conducted in Bangka Belitung and Lampung in FY 2003, with PRAapproach through group discussion technique. This research aims to identify the performance,problems and implementation perspective of Integrated Pest Management (IPM) in pepperfarming system and also to identify socio-economic factors influencing IPM adoption.Through qualitative and quantitative descriptive analysis, shows: (a) Introduction of IPMprinciple not yet entirely adopted by farmer of Field Laboratory-IPM participant; (b)Influencing factors of IPM adoption are covering internal and external factors having thecharacter of technical and non technical namely farmer characteristic, owner of farm status,accessibilities of farming system location and market of input, pepper price, and alsocontinuity of counseling by extension agent of agriculture; (c) Practically farmer did not getadded value of IPM adoption because pepper farmer was sold in form of unsorted product,(d) Reorientation for training curriculum of IPM in FL-IPM and also intensive guidance toencourage farmer in carrying out of IPM is needed.